ANALISIS PENGUKURAN NILAI OVERALL EQUIPMENT EFFECTIVENESS (OEE) PADA MESIN DI PT PROTECH PRESISI SUKSES - Ossa Sutaarga; Muhammad Immamul Khoiron (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2025)
PT. Protech Presisi Sukses, a leading manufacturer in the automotive industry, is committed to continuing to make improvements to its production lines to remain competitive. The company aims to increase the productivity of components that contribute to the production process and optimize daily efficiency in each line. The company uses a Just in Time (JIT) production system to ensure timely delivery of spare parts to customers. Overall equipment efficiency (OEE) is critical to identifying and minimizing labor costs in the production process, thereby ensuring maximum productivity. The three components of OEE are Availability, Performance, and Quality. This study analyzes the problem of labor shortages caused by human factors, machines and material damage. To overcome this, the company uses the overall equipment effectiveness (OEE) method to measure the efficiency of the entire production line. The research results show that the total productivity of PT. Protech Presisi Sukses in January and June is the same for all production lines. This study identifies productivity problems in all production lines, focusing on the number of employees and the number of working hours. The research results show that the company has a high level of productivity, PT. Protech Presisi Sukses is committed to continuing to make improvements to its production line to meet customer demand and maintain competitiveness.